2014
DOI: 10.1002/asia.201301347
|View full text |Cite
|
Sign up to set email alerts
|

Porous Protein Crystals as Catalytic Vessels for Organometallic Complexes

Abstract: Porous protein crystals, which are protein assemblies in the solid state, have been engineered to form catalytic vessels by the incorporation of organometallic complexes. Ruthenium complexes in cross-linked porous hen egg white lysozyme (HEWL) crystals catalyzed the enantioselective hydrogen-transfer reduction of acetophenone derivatives. The crystals accelerated the catalytic reaction and gave different enantiomers based on the crystal form (tetragonal or orthorhombic). This method represents a new approach f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
56
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 52 publications
(60 citation statements)
references
References 67 publications
4
56
0
Order By: Relevance
“…Enantiomeric excesses were different from those previously measured with the βLG biohybrids and, quite surprisingly, the mixture of HEWL and Ir(Cp*) afforded preferentially the S enantiomer of α‐(trifluoromethyl)benzyl alcohol, whereas the mixtures of HEWL and the Ru complexes gave the R isomer as before. The rather poor selectivity of the HEWL + Ru(benz) mixture is in line with previously reported results for other acetophenone derivatives …”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Enantiomeric excesses were different from those previously measured with the βLG biohybrids and, quite surprisingly, the mixture of HEWL and Ir(Cp*) afforded preferentially the S enantiomer of α‐(trifluoromethyl)benzyl alcohol, whereas the mixtures of HEWL and the Ru complexes gave the R isomer as before. The rather poor selectivity of the HEWL + Ru(benz) mixture is in line with previously reported results for other acetophenone derivatives …”
Section: Resultssupporting
confidence: 92%
“…It has been recently shown that association of Ru(benz) and cross‐linked crystals of HEWL catalyse the TH of acetophenone derivatives with variable selectivity . Thus, as a preliminary screening, we examined the ability of crude mixtures of HEWL and hydrolysed M(arene) complexes (M = Ru, arene = benz or p ‐cym; M = Rh or Ir, L = Cp*) at molar ratio 1:1 to catalyse the ATH of TFACP.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most frequently investigated, as molecular templates for the synthesis of artificial protein crystal assemblies, are hen egg white lysozyme (HEWL) crystals. Tabe and co‐workers investigated cross‐linked HEWL crystals for their application as catalytic reaction vessels by accumulating organometallic complexes in the solvent channels of the crystals (Figure ) . The cross‐linked crystals were soaked in a buffer solution containing [Ru(benzene)Cl 2 ] 2 complexes for the preparation of Ru(benzene)‐CL‐HEWL composites.…”
Section: Chemoenzymatic Cascade Reactionsmentioning
confidence: 99%
“…43,44 Postengineering of CLPCs has recently been performed to convert solvent channels into nanovessels for preparation of metal particles or immobilization of organometallic catalysts. 20,41,42 The success of these efforts indicates that protein crystals have further potential to provide new structures and improve the reactivity of CORMs when used as extracellular scaffolds for supporting CO-releasing molecules.…”
Section: ■ Introductionmentioning
confidence: 98%